Incidência, características clínicas/ demográficas e ocorrência de hiperalgesia na neuropatia sensitiva periférica da oxaliplatina em pacientes com câncer colorretal tratados com esquema flox - Godinho, Priscilla de Albuquerque Ribeiro (2018)
Colorectal cancer is the most common malignant neoplasm of the gastrointestinal tract, the second most prevalent for males and the third for females. In the treatment of this type of tumor, oxaliplatin (OXL) stands out because it is contained in the majority of the chemotherapy regimens and because it is the first line in the metastatic type. The most significant side effect of OXL use is the peripheral neuropathy, which, depending on the degree of intensity, causes discomfort, dose limitation and discontinuation of the treatment. Despite the existing data, there is still a deficiency in the characterization of this effect and there is currently no way to treat or prevent it. The objective of this study was to evaluate the incidence and clinical and demographic characteristics of peripheral sensory neuropathy, as well as the occurrence of hyperalgesia in the upper and lower limbs. Also to qualitatively assess the orofacial symptoms reported by the patient in a sample of patients with colorectal cancer treated with the FLOX regimen at “Haroldo Juaçaba Hospital” in the period between 2013 to 2016. This is an observational, longitudinal cohort study in which the eligible patients answered a questionnaire on Acute and Chronic Neuropathy, quantifying sensitivity changes in the upper limbs, lower limbs and orofacial region obtained during the chemotherapy cycles. Neurotoxicity was graded according to NCI version 3 - CTCAE and specific neurotoxicity scale for Oxaliplatin (OSNS). The results showed that neurotoxicity (p<0,05) in the upper limbs showed a significant increase among the three chemotherapeutic cycles evaluated. Lower limb symptoms were more intense and more prevalent when compared to upper limb symptomatology. The quantification of the hyperalgesic response was performed by measuring the LMD (mechanical pain threshold) in the palm (right hand) and the plantar surface (right foot), before chemotherapy first cycle (baseline) at weeks 1, 3 and 5 of cycles 1, 2, 3, 4, 5 and 6 of the FLOX regime. The digital algometer was used to decrease subjective interferences such as emotional factors and determined the mechanical pain threshold in palm and plantar surfaces. The digital pressure algometer measurement had a positive correlation (p <0.05) with the evolution of upper and lower limb symptomatology throughout the chemotherapeutic cycles. Pressure exerted on specific points on the palm of the hand and sole of the feet showed an increase in the sensitivity to the pressure stimulus from the first cycle, being increased until the end of the evaluated period. Pain threshold decreased significantly over time, every week, being more significant in the lower limbs than in the upper limbs. The orofacial symptoms were more prevalent than the symptoms in the upper and lower limbs, starting acutely and remaining until the last cycle analyzed, which is contrary to the literature. It was also observed that histological differentiation (low differentiation) and staging (N and M) were significant (p <0.05) when correlated with the sum of the scores in the upper limbs and lower limbs and variation of the pain threshold. In summary, the use of the questionnaire demonstrated the neuropathic profile in the upper limbs, lower limbs and orofacial region, showing that the symptoms started acutely and were chronified until the end of treatment. It was also seen that the neurotoxicity degree in the lower limbs was significantly higher than in the upper limbs. The evaluation of orofacial symptoms was more prevalent than in the lower and upper limbs, showing a greater importance of these symptoms than is currently described in the literature. In addition, we have also shown that the occurrence of hyperalgesia (decrease in pain threshold) affects upper and lower limbs, being more intense in the lower limbs. Together, the data provide greater information and understanding of the incidence and characteristics of this OXL effect, as well as new evidence regarding pain sensitivity and involvement of the orofacial region.